Diversidad genética y estructura de la población de la raza Charolais en Ecuador a través del pedigrí. - Lozada Rivadeneira, Edwin Fernando (2023)
The evaluation of genetic diversity and gene flow through genealogical information of a population is necessary in genetic improvement programs. The objective of the study was to evaluate the diversity and genetic structure of the Charolais population in Ecuador. Three groups of data were used, the historical population, current population and the reference population. The information for each animal included its own name and registration number, the father's, mother's, and date of birth. The parameters evaluated were the completeness of the pedigree, generation interval, consanguinity, mean relationship, increase in consanguinity and effective population size. For data processing, the ENDOG v4.0 program was used. The completeness of the pedigree decreased considerably from the second generation in both populations, although the first generation showed values of 0.617 and 0.745. The average generation interval was 7.17 years for the historical population and 8.42 years for the current one.